If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -12c + 6 Reorder the terms: 3 = 6 + -12c Solving 3 = 6 + -12c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '12c' to each side of the equation. 3 + 12c = 6 + -12c + 12c Combine like terms: -12c + 12c = 0 3 + 12c = 6 + 0 3 + 12c = 6 Add '-3' to each side of the equation. 3 + -3 + 12c = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 12c = 6 + -3 12c = 6 + -3 Combine like terms: 6 + -3 = 3 12c = 3 Divide each side by '12'. c = 0.25 Simplifying c = 0.25
| X(3+y)=8 | | 4b-6=-10 | | -9p+18=99 | | 80=90x-120 | | -7b+35=-7(4b-5) | | -21-b=6(2b+3) | | 3x-21=-42 | | 14-5b=-2(1+7b)-2 | | 4x^2+15x-1=18 | | 4(h-12)=44 | | 8p+2=-54 | | -7(n-3)+2n=-4n+26 | | -7m-12=-40 | | -2(x+8)+5=-23+x | | 7m-20=15 | | 7x+35=180 | | 72+6x=11(14x+20) | | 7m-24=-24 | | 72+6x=11(14x+50) | | -6x-19=-1 | | 8/9-4/5 | | 2/4/-1/2 | | -6(8n+14)-16n=-18n+54 | | -4x-22=6 | | -7m+11=53 | | 5X-19=-21 | | 12=x-(-2) | | -12=-6+3y | | 5/7=3/x | | -10k=20(1-10k)-20 | | -13m-16=36 | | x^7+9x^7= |